2001
DOI: 10.1614/0043-1745(2001)049[0528:qaoeos]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of emergence of seedlings from buried weed seeds with increasing soil depth

Abstract: Trials were carried out to investigate the effects of seed burial depth on seedling emergence rate of 20 weed species. Marked depth-mediated variation in emergence ability of the different species was observed, together with a general pattern of decreasing emergence with increasing soil depth. At 10 cm, only johnsongrass, velvetleaf, catchweed bedstraw, and cutleaf geranium emerged, albeit only in limited numbers. Species most severely inhibited by burial depth were buckhorn plantain, large crabgrass, common p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
234
6
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(274 citation statements)
references
References 56 publications
32
234
6
2
Order By: Relevance
“…Previous trials under laboratory conditions in a siltloam soil (23% sand, 52% silt, 25% clay) have shown no emergence of barnyardgrass from 10 cm depth without disturbance (Benvenuti et al, 2001), which is not in agreement with the current study. However, this disparity could be explained by differences in soil type, environmental conditions (i.e.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Previous trials under laboratory conditions in a siltloam soil (23% sand, 52% silt, 25% clay) have shown no emergence of barnyardgrass from 10 cm depth without disturbance (Benvenuti et al, 2001), which is not in agreement with the current study. However, this disparity could be explained by differences in soil type, environmental conditions (i.e.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous research on barnyardgrass and jimsonweed determined that fatal germination (i.e. the seed germinates, but the seedling dies before reaching the soil surface; Davis & Renner, 2007) of these weeds was approximately 25% and 17%, respectively, from a depth of 12 cm in a siltloam textured soil (Benvenuti et al, 2001). In fact, Gardarin et al (2010) reported that the % of fatal germination is proportional to the soil structure (i.e.…”
Section: Factorsmentioning
confidence: 99%
“…Results from these studies generally demonstrated that conservation tillage is associated with increased weed pressure [39,52,53]. The enhancement in weed pressure primarily results because inversion tillage tends to distribute weed seeds to a depth from which emergence is unlikely, while non-inversion tillage leaves many weed seeds in the upper soil horizon which enhances the likelihood of emergence [10,53,66]. However, research results have been somewhat variable because of differences in crop management (e.g., crop selection).…”
Section: Organic Zero Tillage Effects On Weedsmentioning
confidence: 99%
“…It is possible that the seed bank contributes minimally to plant establishment because the soils that comprise mounds are from depths below which most viable seeds are found. Moreover, burial of seeds beneath mounds may actually reduce the potential for emergence from the seed bank (e.g., Benvenuti et al, 2001). …”
mentioning
confidence: 99%